The Influence of Content Marketing, Influencer Marketing, and Service Quality on Purchasing Decisions for Fashion Products on Shopee - Zaenal Muttaqin; Bayu Fajar Susanto (Manunggal Halim Jaya, 2026)
This study aims to analyze the influence of content marketing, influencer marketing, and service quality on purchasing decisions for fashion products on Shopee among the people of Pacitan Regency. This research used a quantitative approach with a descriptive research type. The population in this study consisted of people in Pacitan Regency who had purchased fashion products on Shopee. The sample consisted of 150 respondents determined using the Lemeshow formula with a simple random sampling technique. Data were collected through questionnaires using a Likert scale. Data analysis was conducted using IBM SPSS Statistics through validity tests, reliability tests, classical assumption tests, and multiple linear regression analysis. The results showed that content marketing had a positive and significant effect on purchasing decisions, influencer marketing had a significant negative effect on purchasing decisions, and service quality had a positive and significant effect on purchasing decisions. Simultaneously, content marketing, influencer marketing, and service quality significantly affected purchasing decisions for fashion products on Shopee. The R Square value of 0.790 indicates that 79% of purchasing decisions can be explained by the three independent variables, while the remaining 21% is influenced by other variables outside this study.